Tekanan Ekonomi dan Dampaknya Terhadap Kesehatan Mental Anggota Keluarga - Fedri Yani Wulandari; Sabrina Sabrina; Intan Intan; Tya Ariani; Hidayani Syam (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Family economic pressure is a significant predictor of stress, anxiety, and depression in individuals and can affect family relationships as a whole. Factors such as poverty and unemployment are identified as the main causes of economic pressure, so appropriate interventions such as family counseling and economic assistance programs are crucial to help families develop effective coping skills and improve their well-being. This study uses a literature approach through books, articles, journals, and other previous research to examine the impact of economic pressure on the mental health of family members. The results show that family economic pressure has a significant impact on individual mental health and family relationships, and highlights the importance of appropriate interventions to reduce the negative impacts. The findings of this study have important implications for the development of policies and programs aimed at reducing the negative impacts of economic pressure on the mental health of family members.